Analysis of the cost-efficiency of the vascular impulse technology (VIT) in the perioperative management of complex ankle fractures: results of a prospective randomised controlled trial - Barbari, Jan el; Schnetzke, Marc; Swartman, Benedict; Grützner, Paul Alfred; Franke, Jochen (Journal of orthopaedic surgery and research, 2023)
Posttraumatic swelling causes a delay in surgery, a prolonged hospital stay and a higher risk of complications. Thus, soft tissue conditioning following complex ankle fractures is of central importance in their perioperative management. Since the clinical benefit of VIT usage on the clinical course has been shown, it should now be investigated whether it is also cost-efficient in doing so.
Gesehen am 12.12.2023